Dinamika Sosial dan Budaya dalam Penyebaran Narkoba di Jalan Kunti, Kecamatan Semampir, Kelurahan Sidotopo, Surabaya - Ardha Wildan Zulfa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Drug abuse and distribution is a serious problem in Indonesia. including in the Jalan Kunti area, Sidotopo Village, Semampir District, Surabaya.  Prevention of narcotics abuse is also the main goal of the 8th president as stated in Asta Cita number 7. This research aims to examine the social and cultural dynamics in the spread of drugs in the region using Emile Durkheim's Solidarity theory. The method used in this research is using a qualitative case study method approach, data was taken through interviews with former drug users and also anti-drug activists in the area. The results of this research reveal that solidarity mechanisms dominate on Jalan Kunti, which supports the normalization of drug trafficking through loyalty groups and ignores formal laws. Organic solidarity weakens, while economic pressures strengthen community involvement in illegal activities, creating obstacles in efforts to eradicate drugs.